ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI YIELD OBLIGASI KONVENSIONAL DI INDONESIA (Studi Kasus Pada Perusahaan Listed di BEI) - Tiyas Ardian Saputra; Prasetiono Prasetiono (Faculty of Economics and Business Diponegoro University, 2014)
Basically the value of inflation affect bond’s yield. When inflation was increase , so thatbond’s yield will increase as well. However, in 2010 increase of inflation were followedby decrease of bond’s yield. In 2011, when BI rate was increase, also was followed bydecrease of bond’s yield. The aims of this study are to analyze the effect of BI rate,inflation, GDP and bond rating to bond yield.The research use purposive sampling method. Purposive sampling method is a samplingmethod that is based on certain criteria. Sample in this study are 17 samples from 2008to 2011 period. Data for this study can be obtained from Bond Book that are published inIndonesia Stock Exchange (IDX) website. Data analysis use multiple linear regressionwith SPSS 18 software.Based on data analysis can be concluded that BI rate variable have a positive andsignificant impact on bond yield. Inflation variable have a positive and significantimpact on bond yield. GDP variable have a negative and significant impact onbond yield. Bond rating have a negative and significant impact on bond yield.Then, this study also shows BI rate, inflation, GDP and bond rating have significanteffect together on bond yield.Keywords: Bond Yield, BI rate, Inflation, GDP, Bond Rating